2014
DOI: 10.1021/nn502045y
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Sodium and Lithium Ion Battery Anodes from Banana Peels

Abstract: Banana peel pseudographite (BPPG) offers superb dual functionality for sodium ion battery (NIB) and lithium ion battery (LIB) anodes. The materials possess low surface areas (19-217 m(2) g(-1)) and a relatively high electrode packing density (0.75 g cm(-3) vs ∼1 g cm(-3) for graphite). Tested against Na, BPPG delivers a gravimetric (and volumetric) capacity of 355 mAh g(-1) (by active material ∼700 mAh cm(-3), by electrode volume ∼270 mAh cm(-3)) after 10 cycles at 50 mA g(-1). A nearly flat ∼200 mAh g(-1) pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
648
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 818 publications
(672 citation statements)
references
References 111 publications
23
648
1
Order By: Relevance
“…It can be observed that the intensity of this band decreases in the case of the as prepared RGOs when compared to that of GO. The ID/IG ratio of Fe-RGO is 1.19 and Sn-RGO is 1.14, which are higher than that of graphite (ID/IG = 0.34), indicating a highly disordered nature of the RGO sheets and the associated unrepaired edge defects [4]. These results are in coherence with the XRD and FESEM data.…”
Section: Figures 1(a) and (C)supporting
confidence: 80%
See 2 more Smart Citations
“…It can be observed that the intensity of this band decreases in the case of the as prepared RGOs when compared to that of GO. The ID/IG ratio of Fe-RGO is 1.19 and Sn-RGO is 1.14, which are higher than that of graphite (ID/IG = 0.34), indicating a highly disordered nature of the RGO sheets and the associated unrepaired edge defects [4]. These results are in coherence with the XRD and FESEM data.…”
Section: Figures 1(a) and (C)supporting
confidence: 80%
“…Such sloping behaviour can be accredited to the reversible interaction of sodium at vacancies and Stone-Wales (SW) defects [4]. The Fe-RGO and Sn-RGO showed a specific discharge capacity of 202 and 272 mA h g -1 in the second cycle respectively.…”
Section: Electrochemical Performance Vs Na/na +mentioning
confidence: 99%
See 1 more Smart Citation
“…Because Na + ions cannot be easily intercalated into the layers of graphite due to larger radius of Na + , resulting in a low capacity of 31 mAh g −1 , conventional graphite might not be suitable for SIBs 3. However, various amorphous carbon materials including hollow nanostructured carbons,4 carbon nanospheres,5 carbon nanofibres,6 carbon nanosheets,7 porous carbons,8 hard carbon,9 graphene,10 and heteroatom‐doped carbon materials11 are being investigated as anode for SIBs in full swing, benefiting from disordered nanodomains with randomly oriented graphene layers and voids between these domains, which can provide rich active sites for storing Na + 9, 12. Unfortunately, lots of amorphous carbon‐based anode materials are accompanied with low initial columbic efficiency and poor specific capacity at high current density.…”
Section: Introductionmentioning
confidence: 99%
“…10), olivine-type sodium metal phosphates 11 and Prussian blue 12 . For anode materials in SIBs, various carbon materials have been reported because of their relatively high capacity and cyclability [13][14][15] . Among them, graphite is an intriguing material with different lithium and sodium storage properties (372 mA h g À 1 in LIBs, but less than 35 mA h g À 1 in SIBs).…”
mentioning
confidence: 99%